2020
DOI: 10.1113/jp278986
|View full text |Cite
|
Sign up to set email alerts
|

Fast responses to stepping‐target displacements when walking

Abstract: Goal-directed arm movements can be adjusted at short latency to target shifts. r We tested whether similar adjustments are present during walking on a treadmill with shifting stepping targets. r Participants responded at short latency with an adequate gain to small shifts of the stepping targets. r Movements of the feet during walking are controlled in a similar way to goal-directed arm movements if balance is not violated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 49 publications
0
34
2
Order By: Relevance
“…Note that the scales differ from those of a similar plot for the young adults in our previous paper ( Fig. 6 in Zhang et al (2020)) direction of the perturbation has little or no effect on the adjustments (Oostwoud Wijdenes et al 2013). In contrast, in the present study it was found that corrections for lateral shifts were more complete than those for medial shifts.…”
Section: Arm Reaching Versus Foot Steppingcontrasting
confidence: 85%
See 3 more Smart Citations
“…Note that the scales differ from those of a similar plot for the young adults in our previous paper ( Fig. 6 in Zhang et al (2020)) direction of the perturbation has little or no effect on the adjustments (Oostwoud Wijdenes et al 2013). In contrast, in the present study it was found that corrections for lateral shifts were more complete than those for medial shifts.…”
Section: Arm Reaching Versus Foot Steppingcontrasting
confidence: 85%
“…The main difference with the young adults (not shown; for their patterns see Fig. 6 in Zhang et al 2020) is that all muscles in the older adults were more active. This might reflect the reduced muscle strength in the elderly, because activity was expressed in relation to that when exerting maximal force.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Consequently, foot placement adjustments had to be realized during swing, which we expected to undermine the relationship between foot placement and CoM state. Evidence exists that rapid foot placement adjustments are feasible during a stepping task [39], although stability constraints appear to negatively affect responses to large jumps of foot placement targets [40]. In our study, foot placement appeared to be more effectively constrained by the projections during slow walking as compared to normal walking, as reflected by a lower step width variability at the slower speed (see S4).…”
Section: Foot Placement Constrained Walkingmentioning
confidence: 47%